A new species of Ukamenia from Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Gatesclarkeanini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2020)
The genus Ukamenia Oku (1981) was proposed with Simaethis sapporensis Matsumura (1931) from Japan as its type species, which had been originally described in the family Choreutidae. Oku (1981) based the new genus on characters of S. sapporensis that were typical of Tortricidae rather than Choreutidae, notably the naked haustellum (scaled in Choreutidae), among many other characters differing between the two families, such as wing venation, head morphology, and genital form. Oku (1981) assigned his new genus to the tribe Olethreutini, but mentioned that it resembled the genus Gatesclarkeana Diakonoff, 1966. In her extensive study of Australian Olethreutinae, Horak (2006) briefly noted Ukamenia as being referable to Gateclarkeanini.